Faithfulness in Small Matters: A Biblical-Theological Analysis of Luke 16:1–15 - Raulina, Raulina; Gabriel Panjaitan, Geri (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
The pericope in Luke 16:1–15, commonly referred to as the Parable of the Unjust Steward, presents a complex and challenging theological message. This study aims to explore the concept of faithfulness in small matters as taught by Jesus in this passage. By examining the historical, social, and economic background of the New Testament world and analyzing the rhetorical structure and literary features of the text, this research argues that Jesus' primary emphasis is not on cleverness, but on the moral and spiritual integrity required in managing entrusted resources. Faithfulness in minor matters is shown to be a crucial indicator of one’s readiness for greater responsibilities, revealing one's character and spiritual maturity. The passage underscores the Christian disciple’s calling to live a life of integrity, detachment from wealth, and full devotion to God. This study affirms that faithfulness in small matters plays a formative role in shaping the authentic character of a servant of God.